Meropenem-Clavulanic Acid Shows Activity against Mycobacterium tuberculosis In Vivo - England, Kathleen (American Society for Microbiology, 2012)
The carbapenems imipenem and meropenem in combination with clavulanic acid reduced the bacterial burden in Mycobacterium tuberculosis-infected macrophages by 2 logs over 6 days. Despite poor stability in solution and a short half-life in rodents, treatment of chronically infected mice revealed significant reductions of bacterial burden in the lungs and spleens. Our results show that meropenem has activity in two in vivo systems, but stability and pharmacokinetics of long-term administration will offer significant challenges to clinical evaluation.